Accuracy of Hemoglobin Measurement using the SD Biosensor Standard G6PD Analyzer as Point-of-Care in Pediatric Populations in Malaria-Endemic Regions - Kevin Effendi; Rosmayanti Syafriani Siregar; Hendri Wijaya; Olga Rasiyanti Siregar; Arlinda Sari Wahyuni; Ayodhia Pitaloka Pasaribu (Indonesian Journal of Global Health Research, 2025)
Background: Malaria remains a significant public health concern, particularly in endemic regions, is frequently associated with anemia in children. Accurate hemoglobin measurement is crucial for diagnosing anemia, especially in resource-limited settings. This study compares the accuracy of SD Biosensor Standard G6PD Analyzer with Hemocue HB301 System for hemoglobin measurement among children in malaria-endemic areas. Objective: To determine the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (LR+), negative likelihood ratio (LR-), pretest odds, post-test odds, and overall accuracy of the SD Biosensor Standard G6PD Analyzer compared to the Hemocue HB301 System. Method: This cross-sectional diagnostic study involved 325 children aged 6-18 years in Kualuh Leidong District. Secondary data were obtained from a previous study conducted in August 2024, using a total sampling technique. Result: The mean hemoglobin level measured by SD Biosensor Standard G6PD Analyzer (14,22±2,21 mg/dL) was higher than that measured by Hemocue HB301 System (13,45±1,63 mg/dL), with significant difference (p=0,001). The prevalence of anemia detected by SD Biosensor and Hemocue was 12,3% and 11,4%, respectively. The SD Biosensor Standard G6PD Analyzer demonstrated a sensitivity of 70,27%, specificity of 95,14%, PPV of 65%, NPV of 96,14% and an overall accuracy of 92,31%. Conclusion: The SD Biosensor Standard G6PD Analyzer exhibited relatively low sensitivity but high specificity compared to Hemocue HB301 System in measuring hemoglobin levels among children in malaria-endemic areas. Further research is needed to compare both devices against the gold-standard automated hematology analyzer and to identify the factors influencing measurement accuracy. Keywords: Anemia, Hemocue HB301 System, Hemoglobin, Malaria, SD Biosensor Standard G6PD Analyzer